Effective Palliative Care in the Trauma Setting. Issue 11 (November 2020) - Schultz, Kristen L.; Brasel, Karen J.; Zonies, David H.; Cook, Mackenzie R.
A 55-year-old man undergoes emergent exploratory laparotomy and splenectomy following a motorcycle collision. Following surgery, he is found to have a traumatic brain injury requiring decompressive craniectomy and intracranial pressure monitoring. The patient then continues to have complications throughout his hospital course. Using the American College of Surgeons Trauma Quality Improvement Program guidelines, the surgical team has early and ongoing primary palliative care discussions to foster communication and determine goals of care for the patient. As the patient deteriorates, the surgical team continues meeting with the patient's surrogate decision makers to discuss the best case and worst case scenarios regarding the patient's prognosis and expected quality of life.